Kalbotyros straipsnių sąsajos su kitais mokslo tekstais - Kontutytė, Eglė (Vilnius University Open Series, 2023)
Scholarly text conventions are important when writing texts, especially in a foreign language. Intertextual relations with other texts are a characteristic feature of scientific language. As Lithuanian and foreign researchers point out, this is manifested by quoting, paraphrasing and summarizing. In examining the intertextuality of academic language, researchers also draw attention to its multilingualism. Based on the above-mentioned forms of intertextuality, this article analyses the intertextuality features of linguistics articles written in Lithuanian. The analysis shows that direct quotations in Lithuanian articles include short phrases or even full sentences from other authors’ texts imbedded in a sentence, with or without introductory phrases. In English, Polish or Russian, direct quotations can also be inserted into a sentence. Quotations from other languages are given with or without translation. Paraphrasing has been observed to be more frequently used, as the reformulated statements of other authors do not destroy the linguistic integrity and cohesion of the text. This is especially useful when quoting texts in other languages. A reference is one in which the text does not directly or indirectly reproduce the statements of other authors, but merely refers in some way to previous research. Scholarly terms from other languages, usually English, presented as equivalents of other languages together with the Lithuanian term or even without it., may be treated as a case of multilingual intertextuality. Although precision is often pointed out as a feature of academic language, the linguistics articles analyzed show many instances of paraphrasing and referential intertextuality. Such intertextual interfaces substantiate the research presented in the article or the scientific issues raised, establish their place within a wider range of sources, and convey the author’s thought in a condensed way in the language of the publication, without breaking the typographic and linguistic unity of the text. Multilingual intertextuality shows that it is important for researchers of the Lithuanian language, who publish their texts in Lithuanian, to locate their research in the international context of linguistics and to establish a scientific dialogue with researchers of other countries and languages.